Tap Playing Style of Nai Tap Sommai La-ongsom in Nora Performance / ลีลาการตีทับของนายทับสมหมาย ละอองสม ในการแสดงโนรา - กนกวรรณ ขวัญยืน, Kanokwan Khwanyuen / (Journal of Community Development Research (Humanities and Social Sciences), 2016)
บทคัดย่อ      งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาความสำคัญของทับและนายทับในวัฒนธรรมโนรา โดยศึกษาลีลาการตีทับของนายทับสมหมาย ละอองสม ในการแสดงโนรา เพื่อแสดงให้เห็นภูมิปัญญาของนายทับชั้นครู และเพื่อเสนอแนวทางส่งเสริมและอนุรักษ์ลีลาการตีทับในวัฒนธรรมโนราให้คงอยู่ ทั้งนี้ ผู้วิจัยประยุกต์ใช้แนวคิดทางมานุษยวิทยาการดนตรีและแนวคิดภูมิปัญญาพื้นบ้านในการวิเคราะห์ข้อมูลวัฒนธรรมดนตรี ใช้ระเบียบวิธีวิจัยเชิงคุณภาพ เน้นการทำงานสนามในพื้นที่ที่นายทับสมหมาย ละอองสม ไปแสดงโนรา      ผลการศึกษา พบว่า ทับ คือเครื่องดนตรีที่เป็นหัวใจหลักของการแสดงโนรา มีหน้าที่ควบคุมจังหวะและเป็นตัวนำเครื่องดนตรีชิ้นอื่น ให้เปลี่ยนจังหวะตามการรำและการทำบทของโนรา นายทับหรือคนตีทับจึงมีความสำคัญที่สุดของวง โนราเป็นรูปแบบของการแสดงที่ผู้รำบังคับดนตรี ดังนั้น ลีลาการตีทับของนายทับจึงขึ้นอยู่กับลีลาเฉพาะบุคคลและลักษณะการรำของโนราเป็นหลัก ซึ่งมีสองรูปแบบ คือ การตีทับแบบเรียบร้อยและการตีทับแบบรุก นายทับที่มีความรู้แตกฉานและมีประสบการณ์มากจะสามารถตีทับได้ทั้งสองรูปแบบ ดังเช่น นายทับสมหมาย ละอองสม หรือลุงอ้อม เป็นนายทับที่มีลีลาการตีทับที่เข้าถึงจิตวิญญาณของโนรา มีทางทับที่เป็นเอกลักษณ์เฉพาะ จนได้รับการยอมรับจากคนในวัฒนธรรมโนราให้เป็นนายทับชั้นครูคนหนึ่ง นอกจากนี้ยังพบว่า ลีลาการตีทับของนายทับสมหมาย ละอองสม ในการแสดงโนรา ส่วนใหญ่มีลักษณะของการซ้ำท้ายเพื่อควบคุมจังหวะหลัก มีการตีลักจังหวะ และมีการตกแต่งทางทับไปตามลักษณะลีลาของผู้รำและบริบทของการแสดง             คำสำคัญ : ทับ  ลีลา  การตีทับ  นายทับ  การแสดงโนรา  สมหมาย ละอองสม   Abstract The purpose of this research was to examine the significances of Tap (Thai percussion instrument used in Nora performance as a lead instrument) and Nai Tap (a percussionist) in Nora culture. The research focused on Tap playing style of Nai Tap Sommai La-ongsom in Nora performance in order to explain anintellect of anexperienced Nai Tap and suggest ways to support and preserve Tap playing style in Nora culture. By this, ethnomusicology concept and folk wisdom were deployed to analyze information about musical culture. Besides, qualitative research methodology and fieldworks where Nai Tap Sommai La-ongsom had his performances were selected as research methods for collecting data. The results revealed that Tap is an important musical instrument in Nora performance. It has main functions of keeping the rhythm and conducting other musical instruments to play depending on how the performers dance. Therefore, Nai Tap is the most significant person in the ensemble. Since Nora is a performance that the performers control the music, Tap playing style of Nai Tap then is decided by the performers’ individual dancing style. There are two styles of playing Tap in Nora performance: simple style and dramatic style. An expert one could play Tap in both styles. Nai Tap Sommai La-ongsom or Lung Om, for example, is a skillful Nai Tap who could predict what the performers would express to the audiences. He has his own unique Tap playing style which causes him to be respected by people who are related to Nora culture as the idol for people in the next generation. The findings also added that Nai Tap Sommai La-ongsom repeats the same tune so that he could control the main rhythm and he sometimes intends to play not to synchronize with the rhythm in order to create melodiousness and excitement to the audiences. Also, he creates his playing style depending on how the performers dance and the context of the performance.   Keywords: Tap, style, Tap playing, Nai Tap, Nora performance, Sommai La-ongsom
Keywords: ทับ ลีลา การตีทับ นายทับ การแสดงโนรา สมหมาย ละอองสม Tap, style, Tap playing, Nai Tap, Nora performance, Sommai La-ongsom